Unraveling the Intricate Dynamics of Turkish Immigrants and Muslim Minorities in Germany - Suganda, Asep Dadan; Lestari, Widianti; Sulthani, Dinil Abrar (LP2M - Universitas Islam Negeri Walisongo Semarang, 2023)
Germany's cultural and economic diversity is enhanced by the contributions of Turkish immigrants and Muslim minorities, whose legacy enriches the country. However, social exclusion and unfavorable preconceptions impact some of these groups, which can hurt their well-being and quality of life. This article addresses the dynamics of Muslim minorities and Turkish immigrants in Germany, emphasizing the social developments, historical trajectory, and difficulties these groups encounter in German society. It focuses on minority rights, social integration, and acceptance. This article employs a qualitative descriptive technique, interpreting qualitative data in-depth to comprehend and explain social phenomena or human behavior. Data is gathered by analyzing pertinent materials and subsequently interpreted thematically in light of the study environment. This article's conclusions and discussions are restricted to the impact of Turkish immigration on the Muslim community while considering a range of social, cultural, political, and economic facets of German life. Karl Marx's conflict theory holds that these difficulties reflect underlying power dynamics and class struggles, in which the dominant class keeps control over resources, cultural norms, and political authority, resulting in systemic conflicts and inequality. In addition to initiatives to support equality and inclusion, addressing these concerns calls for a greater comprehension of the structural dynamics at play.